2011
DOI: 10.1177/1757177411411124
|View full text |Cite
|
Sign up to set email alerts
|

Hand hygiene knowledge and attitudes: comparisons between student nurses

Abstract: It is recognised that early intervention in healthcare workers’ education is important in terms of embedding effective infection prevention and control knowledge into practice. One of the most important aspects of this education is hand hygiene compliance and technique expectations. This small study was undertaken in collaboration with the University of Dundee, School of Nursing and Midwifery and NHS Tayside. It explored the differences in knowledge, attitudes and practice towards hand hygiene among second and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 21 publications
0
9
0
Order By: Relevance
“…3 Further increase in compliance is difficult to sustain, although the World Health Organization (WHO) has compiled guidelines in this regard in order to reduce the prevalence of health care associated infections. 3 Furthermore, many studies done to assess the knowledge, attitudes, compliance and reasons for non-adherence to hand hygiene guidelines have found that compliance with hand hygiene protocols by health care workers (HCW) is poor 4,5,6 due to several constraints, including heavy work load, high number of clinical procedures and skin conditions of the HCW. 7,8 An alarming revelation was that compliance was found to be worst before highrisk procedures.…”
Section: Introductionmentioning
confidence: 99%
“…3 Further increase in compliance is difficult to sustain, although the World Health Organization (WHO) has compiled guidelines in this regard in order to reduce the prevalence of health care associated infections. 3 Furthermore, many studies done to assess the knowledge, attitudes, compliance and reasons for non-adherence to hand hygiene guidelines have found that compliance with hand hygiene protocols by health care workers (HCW) is poor 4,5,6 due to several constraints, including heavy work load, high number of clinical procedures and skin conditions of the HCW. 7,8 An alarming revelation was that compliance was found to be worst before highrisk procedures.…”
Section: Introductionmentioning
confidence: 99%
“…In a study carried out in Turkey among university students frequency of hand washing was found to be 6-10 times a day, another study found only 41.4 % of participants wash their hands 11 times a day which was recommended as the cut off point for proper hand washing. 3,5 In our study 39.4 % participants wash their hands 6-10 times a day.…”
Section: Discussionmentioning
confidence: 50%
“…The questionnaire is prepared by using previously published studies. 5,7 Questionnaire was pretested to validate questions and necessary amendments were done to obtain feasible responses. The questionnaires were filled in the presence of investigator in a separate session.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, many studies done to assess the knowledge, attitudes, compliance and reasons for nonadherence of HH by health care workers;denoted pooradherence to HH,due to several constraints including; high number of clinical procedures, lack of appropriate equipment, low staff to patient'ratios, allergies to hand washing products, and insufficient knowledge among staff about risks procedures,the time required and casual attitudes among HCWs towards bio-safety (15,16,17) .Students in their clinical training phase throughout the healthcare facilities can potentially transmit infections besides being the healthcare providers of future, their patterns of training will reflect on their infection control practices. Multiple studies that have been conducted to study HHpractices among nursing and medical students, found that medical students have anoverall lower rate of HH, compared to nursing students (18,19) .…”
Section: Introductionmentioning
confidence: 99%